STUDI FENOMOLOGI: PEMAHAMAN PERPAJAKAN, TARIF PENGENAAN PPH 21 DAN SANKSI PAJAK TERHADAP PELAKSANAAN WAJIB PAJAK ORANG PRIBADI PEGAWAI DINAS PERHUBUNGAN KOTA SURAKARTA - Amelia Romandhoni Novitasary; Erma Setiawati (JURNAL ILMIAH EDUNOMIKA, 2025)
Tax is a payment obligation that is the main source of state revenue, which is used by the government to fund development projects and government spending. This study aims to analyze how the understanding of taxation, the imposition of PPh 21 rates and tax sanctions on the implementation of individual taxpayers of the Surakarta City Transportation Service. This study uses a descriptive analysis method with a qualitative approach. This is because this study aims to understand social phenomena or symptoms by focusing more on a complete picture of the phenomenon being studied. While the data collection methods used are interviews and observation. Overall, the informants understand the importance of tax obligations and the benefits of tax compliance. Although there are still some obstacles in reporting and paying taxes. PPh 21 as an income tax has a progressive rate system and is considered fair by the informants, although it’s still necessary to improve understanding and supervision to ensure optimal tax compliance. Tax sanctions consist of administrative fines and criminal sanctions that can increase taxpayer compliance if implemented properly. However, there’s still limited understanding of tax sanction among taxpayers.